Surface functionalization of conjugated microporous polymer thin films and nanomembranes using orthogonal chemistries. Issue 18 (14th January 2016) - Lindemann, P.; Schade, A.; Monnereau, L.; Feng, W.; Batra, K.; Gliemann, H.; Levkin, P.; Bräse, S.; Wöll, C.; Tsotsalas, M.
Abstract : The synthesis and surface modification of CMP thin films and nanomembranes was performed using orthogonal click chemistries. The surface modification can tune the nanomembrane properties for desired applications; the use of photo-initiated reactions provides the additional opportunity to photo-pattern the CMP materials. Abstract : Conjugated microporous polymers (CMP) have attracted large interest due to their intrinsic porosity, outstanding stability and high variability. Here we present the surface modification of CMP thin films and nanomembranes via orthogonal chemistry. Using the light induced thiol–yne reaction for the functionalization provides the additional opportunity to photo-pattern the CMP materials.